Factors associated with ever smoking among students in Tamil primary schools in Kuala Lumpur, Malaysia - Thestnamoothi, Jivita (2016)
The Ministry of Health, Malaysia has conducted “Say No” as anti-smoking campaign in order to avoid Malaysian population especially school children from smoking. However, the prevalence of smoking was high among secondary school students and they usually started smoking during primary school. But, there is limited study on smoking among primary school children in Malaysia. Thus, this study was conducted to determine the factors associated with ever smoking (ever smoked even for a puff) among Indian students at Tamil primary schools in Federal Territory of Kuala Lumpur. A cross-sectional study was conducted among 665 Indian students of age 10 and 11 years old in seven Tamil primary schools in Kuala Lumpur using cluster sampling from July to September 2014. Data collection used guided self-administered questionnaires. Section A was asked about characteristic of respondents, Section B was family background, Section C was influencing factors, Section D was history of smoking, Section E was knowledge of smoking. Ever smoking was defined as respondents who had history of smoking at any time regardless of frequency or amount even one puff or duration. Current smoker was defined as respondents who reported to smoke at least one cigarette every day in a week. The independent variables were characteristic of respondents, family background, influencing factors, and knowledge on smoking. Data were analyzed using International Business Machine Statistical Package for Social Sciences version 21 (IBM SPSS). Descriptive analysis used frequency and percentage to summarize the categorical data. The chi-square or Fisher‟s exact test was used to determine the association between categorical variables and ever smoking. Multiple logistic regression was used to determine the factors associated with smoking. The overall response rate for the study was 86.6%. The percentage of ever smoking was 10.5 % (95% CI: 8.2, 12.8), whereas, the percentage of current smoker was 1.7 % (95% CI: 0.7, 2.7). The median (interquartile range) of age of smoking initiation was 9.00 (3.00). The main reason of smoking was curiosity (62.9%). Factors significantly associated with ever smoking were being male (AOR= 2.17, 95%CI: 1.07, 4.40), aged 11 years old (standard 5) (AOR= 2.05, 95%CI: 1.08, 3.86), having 5 and more siblings (AOR = 3.23, 95%CI: 1.41, 7.40), having father who is a smoker (AOR = 2.96, 95%CI: 1.57, 5.58), having mother who is a smoker (AOR = 7.12, 95%CI: 1.41, 36.04), having friends who smokes (AOR = 7.08, 95%CI: 3.74, 13.42), those who smoke if friends offered a cigarette (AOR = 7.16, 95%CI: 2.35, 21.80), and students with knowledge on smoking can cause bad breath (AOR = 3.37, 95%CI: 1.12, 10.08). In conclusion, there is about one-tenth of Indian primary school students ever smoked in this study. Smoking behaviour among family members and friends were the important factors of ever smoking among Indian students in Tamil primary schools. Cohort study is needed to confirm the factors associated with the risk of smoking among Indian primary school students.